2021
DOI: 10.1177/17590914211010628
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Cord Mesenchymal Stem Cells-Secreted TSG-6 Is Anti-Inflammatory and Promote Tissue Repair After Spinal Cord Injury

Abstract: Spinal cord injury (SCI) causes patients paralysis and hard to recover. The therapeutic effects of current clinical drugs are accompanied by side effects. In recent years, stem cell therapy has attracted the attention of researchers. Human umbilical cord mesenchymal stem cells (hucMSCs) have been widely used in various diseases due to their excellent paracrine function. TNF-stimulated gene 6 (TSG-6), a secretion factor of stem cells, may play an important role in hucMSCs in the treatment of SCI. So we conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Moreover, the original evidence that TSG-6 produced by MSCs underlies their immunomodulatory and reparative functions [ 104 , 105 ] has stimulated interest in understanding the role of this molecule in a number of pathological conditions. Indeed, an increasing body of experimental evidence suggests that the main function of this protein is to protect tissue from the damaging effects caused by inflammation, as demonstrated in animal models of acute myocardial infarction [ 104 ], atherosclerosis [ 106 ], lung injury [ 107 , 108 ], arthritis [ 109 , 110 , 111 , 112 , 113 ], spinal cord injury [ 114 ], and, most notably, acute brain injury [ 115 , 116 , 117 , 118 , 119 , 120 ].…”
Section: Biological Effects Of Tsg-6mentioning
confidence: 99%
“…Moreover, the original evidence that TSG-6 produced by MSCs underlies their immunomodulatory and reparative functions [ 104 , 105 ] has stimulated interest in understanding the role of this molecule in a number of pathological conditions. Indeed, an increasing body of experimental evidence suggests that the main function of this protein is to protect tissue from the damaging effects caused by inflammation, as demonstrated in animal models of acute myocardial infarction [ 104 ], atherosclerosis [ 106 ], lung injury [ 107 , 108 ], arthritis [ 109 , 110 , 111 , 112 , 113 ], spinal cord injury [ 114 ], and, most notably, acute brain injury [ 115 , 116 , 117 , 118 , 119 , 120 ].…”
Section: Biological Effects Of Tsg-6mentioning
confidence: 99%
“…Among its various activities, TSG-6 regulates immune and stromal cells functions and affects extracellular matrix assembly and interaction with cell surface receptors and soluble mediators (e.g., chemokines) [ 23 ], exerting anti-inflammatory and immunosuppressive effects in diverse pathological contexts, including neuroinflammation [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Accordingly, this protein protects tissues from the injurious effects caused by spinal cord injuries [ 32 ] and, most notably, acute cerebral injuries [ 33 , 34 , 35 , 36 , 37 , 38 ]. Notably, TSG-6 expression is elevated in the peri-infarct and infarcted brain tissue of stroke patients [ 39 ] and in the plasma of non-cardioembolic acute ischemic stroke patients, where it is positively associated with disease severity and lesion volume [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…The MSCs are the progenitor/stem cells that have the capacity to differentiate into multilineage cells (Billing et al, 2016 ; de Castro et al, 2019 ). Due to their potential for differentiation, their immunomodulatory effect, and their regeneration capacity (Zhang et al, 2020a ; Oh et al, 2021 ), they are widely used in treating injuries and some inflammatory disorders (Zhang et al, 2020a ; Liao et al, 2021 ). Clinical studies have shown that because of the immunomodulatory function of some subsets of MSCs, MSC therapy could suppress the immune system and treat inflammatory and autoimmune diseases (Nauta and Fibbe, 2007 ; Yang et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%